Pengaruh Penggunaan Abu Cangkang Kelapa Sawit Pada Batako Terhadap Nilai Kuat Tekan Dan Penyerapan Air - David Sarana; Sofyan; Farhan Wini Sara; Syibral Malasyi; Hafli, Teuku Mudi; M Fauzan (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
Concrete block is a building element made from a mixture of Portland cement or pozzolan, sand, water, and other additives. This study aims to evaluate the effect of adding palm shell ash as a partial cement substitution material on the compressive strength and water absorption of concrete block according to SNI 03-0349-1989. The variations of palm shell ash substitution used were 5%, 10%, 15%, and 20% of the cement weight. The test results showed that the average compressive strength values for the BN (normal), BA-5, BA-10, BA-15, and BA-20 variations were 8.88 MPa, 12.2 MPa, 7.9 MPa, 7.2 MPa, and 6.7 MPa, respectively. The optimum compressive strength value was achieved in the BA-5 variation with a value of 12.2 MPa and was included in the classification of quality I concrete block. A decrease in compressive strength occurred in variations above 5%, but still met quality standards I and II. The water absorption test showed consecutive values of 10%, 10.5%, 13.4%, 13.2%, and 15.3%, where all variations were still below the maximum limit of 25% according to SNI and categorized as quality I. Thus, palm shell ash has the potential to be a cement substitute in making bricks, especially at a content of 5%, which provides the best mechanical and physical performance.